Aging with diabetes: Sense of coherence and satisfaction with life in european older adults with type 2 diabetes - von Humboldt, Sofia (2013)
ABSTRACT -- Objectives: The population’s increased longevity is leading to a worldwide concern about older adults’ well-being and about the incidence of chronic diseases such as diabetes. The present research intends to: (a) determine significant differences among three groups of older adults with diverse diabetes diagnosis, namely, participants with only type 2 diabetes, participants with diabetes and other chronic diseases and the remaining without any chronic disease, regarding the satisfaction with life (SWL) and sense of coherence (SOC) scores, and (b) to assess the association of SWL with SOC in these groups. Method: We recruited 304 non-institutionalized older adults aged between 74-100 years (M=82.9; SD= 6.71), who were allocated to three groups, according to their diagnosed medical condition. Measures were completed, including demographics, the Satisfaction with Life Scale and the Orientation to Life Questionnaire. Results: Significant differences were found regarding the SWL and SOC among the three groups. The lowest SOC and SWL scores were found in the ‘only diabetes’ group. Findings also indicated the existence of an association between SOC and SWL scores in the with ‘only diabetes’ group. No correlations were found between SOC and SWL scores in the ‘without diabetes’ and ‘with diabetes and other’ groups. Conclusions: Findings suggest that chronic diseases such as diabetes, as well as the existence of comorbidities, differently influence both SWL and SOC. Furthermore, this study discloses the importance of SWL and SOC for the elderly, in particular when in the presence of diabetes, and their relevance in the context of healthy aging in older populations.